Understanding the Exchange of Systemic HDL Particles Into the Brain and Vascular Cells Has Diagnostic and Therapeutic Implications for Neurodegenerative Diseases - Van Valkenburgh, Juno; Meuret, Cristiana; Martinez, Ashley E.; Kodancha, Vibha; Solomon, Victoria; Chen, Kai; Yassine, Hussein N. (Frontiers in Physiology, 2021)
High-density lipoproteins (HDLs) are complex, heterogenous lipoprotein particles, consisting of a large family of apolipoproteins, formed in subspecies of distinct shapes, sizes, and functions and are synthesized in both the brain and the periphery. HDL apolipoproteins are important determinants of Alzheimer’s disease (AD) pathology and vascular dementia, having both central and peripheral effects on brain amyloid-beta (Aβ) accumulation and vascular functions, however, the extent to which HDL particles (HLD-P) can exchange their protein and lipid components between the central nervous system (CNS) and the systemic circulation remains unclear. In this review, we delineate how HDL’s structure and composition enable exchange between the brain, cerebrospinal fluid (CSF) compartment, and vascular cells that ultimately affect brain amyloid metabolism and atherosclerosis. Accordingly, we then elucidate how modifications of HDL-P have diagnostic and therapeutic potential for brain vascular and neurodegenerative diseases.